New mutation causing androgen insensitivity syndrome – a case report and review of literature. (3rd April 2019) - Maciejewska-Jeske, Marzena; Rojewska-Madziala, Patrycja; Broda, Karolina; Drabek, Karolina; Szeliga, Anna; Czyzyk, Adam; Malinger, Stanislaw; Kostrzak, Anna; Podfigurna, Agnieszka; Bala, Gregory; Meczekalski, Blazej; Malcher, Agnieszka; et al.
Abstract: Androgen insensitivity syndrome (AIS) is a congenital disorder in which a defect in the androgen receptor (AR) gene leads to cellular resistance to androgens. Defects in the AR gene, located on the X chromosome, result in the development of a feminine phenotype in chromosomally male (46, XY) individuals. In this case report, we present a 44 years old patient with complete androgen insensitivity syndrome (CAIS) initially presenting with primary amenorrhea. The patient underwent a full clinical evaluation, revealing hypoplastic vagina and a lack of uterus and ovaries. Hormonal evaluation revealed markedly elevated testosterone, FSH, and LH serum concentrations. Diagnostic imaging, including pelvic MRI, confirmed the presence of two solid masses in the inguinal canals (right 26 × 13 mm, left 25 × 15 mm). The patient underwent genetic testing, revealing a 46 XY karyotype and an as of yet unprecedented androgen receptor mutation. The type of the mutation was a single-base exchange – the substitution from cytosine to thymine in chromosome X:66942710 position (referred to human reference genome GRCh37), which has resulted in an amino acid changes from leucine (CTT) to phenyloalanine (TTT) in ligand-binding domain.